Acute ureteral occlusion. Experimental study - Vidal, Hugo; Campos, Néstor; Piñeiro, José; Reyes, Ismael; Beckerman, Carlos; Siguenza, R; Páez, A; Touya, Juan J (Cirugía del Uruguay, 1972)
By means of serious renal interlography, the aim is to find a non-invasive means to elucidate the problem of ureteral occlusion and acute arterial obstruction.